Differences in the Concentration of Micronutrients in Young Shoots of Numerous Cultivars of Wheat, Maize and Oilseed Rape - Jolanta Korzeniowska; Ewa Stanislawska-Glubiak (Agronomy, 2022)
Individual species of cultivated plants differ in the content of microelements in the shoots. The aim of our research was to test the hypothesis that the variability of the micronutrient content between cultivars of the same species may be similar or even greater than the differences between species. The research material consisted of shoot samples of 12 wheat, 10 maize and 12 rape varieties collected from production fields in Poland. The smallest number of samples (replicates) within one cultivar was 10. A total of 481 wheat samples, 141 maize samples and 328 rapeseed samples were taken. Wheat samples were taken at the beginning of the stem elongation stage (BBCH 30/31); maize, when the plants reached a height of 25–30 cm (BBCH 14–15); and rape, in the period from the beginning of the main stem elongation stage to the appearance of the first internode (BBCH 30/31). All varieties of the tested crop species were grown in similar soil conditions in terms of pH, texture and TOC content. B, Cu, Fe, Mn and Zn were determined in all plant samples. Wheat showed a significantly lower average concentration of all micronutrients compared to rape and maize (e.g., 10 times less B than rape). On the other hand, among the species tested, rape had the highest concentration of B, Cu and Zn, and maize had the highest concentration of Fe and Mn. In all three tested crops, the differences in the content of B and Zn were greater between species than between cultivars. In the case of Cu, Mn and Fe concentration, the cultivar differences exceeded the species differences. The results suggest that there is no need to take cultivars into account when fertilizing with B and Zn. In contrast, fertilization with Cu, Mn and Fe needs to take into account different requirements of the cultivars for these micronutrients.